2013
DOI: 10.1371/journal.pone.0064345
|View full text |Cite
|
Sign up to set email alerts
|

Low Primary and Secondary HIV Drug-Resistance after 12 Months of Antiretroviral Therapy in Human Immune-Deficiency Virus Type 1 (HIV-1)-Infected Individuals from Kigali, Rwanda

Abstract: Treatment outcomes of HIV patients receiving antiretroviral therapy (ART) in Rwanda are scarcely documented. HIV viral load (VL) and HIV drug-resistance (HIVDR) outcomes at month 12 were determined in a prospective cohort study of antiretroviral–naïve HIV patients initiating first-line therapy in Kigali. Treatment response was monitored clinically and by regular CD4 counts and targeted HIV viral load (VL) to confirm drug failure. VL measurements and HIVDR genotyping were performed retrospectively on baseline a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
32
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 33 publications
6
32
3
Order By: Relevance
“…found that M184V was predominant (43.6%) in Kenya , and the predominance of M184V and K103N was found by Rusine et al . and Ziada El‐Khatib . However, the predominance of K65R in our study differs from other studies mentioned due to use of TDF instead of thymidine analogue‐based regimen.…”
Section: Discussioncontrasting
confidence: 90%
See 3 more Smart Citations
“…found that M184V was predominant (43.6%) in Kenya , and the predominance of M184V and K103N was found by Rusine et al . and Ziada El‐Khatib . However, the predominance of K65R in our study differs from other studies mentioned due to use of TDF instead of thymidine analogue‐based regimen.…”
Section: Discussioncontrasting
confidence: 90%
“…Viral suppression results were comparable to those found by Rusine et al . in a smaller prospective cohort of 213 patients on ART in Kigali where 86% achieved HIV viral suppression . Another retrospective study conducted in Rwanda by Frank et al .…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…These findings are slightly better than the 29% failure we observed at 12 months. Notably, these outcomes are worse than recent reports from general adult ART clinics ranging from 9 to 16% virologic failure [31-33]. Other pregnancy-related studies have reported a high rate of loss from follow-up, but have not included virologic outcomes [14, 16, 34].…”
Section: Discussionmentioning
confidence: 97%